Beyond Entertainment: Gastrodiplomacy Performance in Korean Drama and Reality Show - Vellycia Vellycia (Communicare : Journal of Communication Studies, 2021)
ABSTRACT As the world keeps advancing due to globalization, countries across the world were competing against each other to be more acknowledgeable. The use of nation branding appears to be better suited to solve that problem. The use of public diplomacy such as gastrodiplomacy is believed to be the perfect tool in achieving that goal. South Korea was one of the many countries to do so. The country does not solely rely on the concept of gastrodiplomacy alone, rather it combines diplomacy with the use of media and entertainment industry.  This research aims to elaborate the use of Korean television programs as the medium for cultural representation through gastrodiplomacy performed within. This research attempts to interpret gastrodiplomacy performances within the Korean drama, ‘Weightlifting Fairy: Kim Bok-Joo’ and Korean reality show, ‘BTS: In The Soop’ by applying diplomacy and performance concept, and food as nation branding theory. This study shows that television drama and reality show were able to create an engagement and connection with their audience, making both shows effective in delivering the message. The research will be carried out using qualitative research measurement, by analyzing the food appearances happening within the selected scenes from both the series.